PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA EMPRESA DEDICADA A LA ELABORACIÓN Y COMERCIALIZACIÓN DE ACUARIOS Y GABINETES DE BAÑO EN LA CIUDAD DE LOJA - Rivera Bao, Carlos Alberto (2016)
The research was conducted in the city of Loja, aiming at presenting a proposal to “DRAFT FEASIBILITY STUDY FOR THE IMPLEMENTATION OF A COMPANY DEDICATED TO THE DEVELOPMENT AND MARKETING OF AQUARIUMS AND CABINETS BATH CITY Loja” Chosen this topic because in our country and specifically in the city of Loja, the industrial sector has been the engine shaft generator of employment and economic and social growth. That is why the creation of this company is proposed that by exploiting the resources that are in our city, like to address this shortcoming is to implement industry with a complete technical management study, in the manufacturing business area such as the creation of articles made of glass and derivatives thereof in order to encourage employment opportunities and break the traditional structure it is considered to big cities such as business development center. A brief outline of how to implement the idea of this company came, and the importance of contributing to the development of the province of Loja is presented in the introduction. Then the Materials and Methods techniques information collection and research methods that were used for the preparation of this study are indicated. The Market Research market segment the families, obtaining a sample of 400 families surveyed, which allowed to obtain necessary information about the product and the demand for it. With the completion of the market study it was determined that the potential demand for aquariums is 46.045 families; a real demand for aquariums 44.663; effective demand of 39.304 aquariums. Whereas the average annual use is two family resulting effective annual demand of 39.304. Likewise interviews applied direct competitors of our product in the city of Loja is the same as 25,688; also offering for the following year life of the project with 10% estimation personal. Proving the existence of an unsatisfied demand for 14.657 in a year.Based on the results of the market study Aquariums occur in large size 70cm wide x 50 high rectangular shape, glass and essential product is seen by the consumer through the prism of conditioning your home, it provides and "ensures".A friendly and welcoming atmosphere in your home with the charisma of maritime vegetation in your own home without having to be at sea. Regarding prices will be comfortable considering the price competition, production costs and profit margin. At the same time the company will feature a logo and slogan. The distribution channel is producer, intermediary and end user. Advertising is executed on the local television. The Technical Study made the size and location of the project was determined by attaching the sketch of the location of the land and the plane of the physical layout of the plant, the engineering project is the production process in all its phases ; also the most suitable for making high quality aquariums technological alternatives discussed. Also the location of the company is established, is located in the parish of San Sebastian.Regarding Organizational and Management Study, the legal organization intends establishing the company as a corporation will have two partners, whose corporate name is "The Palace of Aquarius CIA LTA", in administrative and study the administrative organization arises through charts and manual functions. The Financial Studio is stated that the creation of the company, “The Palace of Aquarius SA “a $ $ 29,277.66 is required. The founding partners bring in $ 8,783.30 representing 30 % of the investment and the difference with a credit for the amount of $ 20,494.36 representing 70 % of the investment total. The Income Statement shows a net income of $ 12,273.39 in the first period and go on increasing in the following years. The cash flow is $ 14,767.82 in the first year and in the same way the cash requirements for the remaining years of life of the project is determined.The evaluation of the project showed that the net present value is positive with a value of $ 34,450.64 ; the internal rate of return of 65.39 % is greater than the opportunity cost of capital of 12 % , the cost-benefit ratio indicates that for every dollar spent 28 cents of performance will be obtained , the investment will pay off in 2 years, 0 months and 0 days; and , based on the sensitivity analysis demonstrates a satisfactory result allowing 14.14 % increase in costs and a decrease in revenue of 11.25 %. The results obtained in this project demonstrate the feasibility and cost of creating a company dedicated to the development and marketing of bathroom cabinets and aquariums in the city of Loja.